ALTERNATIVE LOCATION ANALYSIS FOR RELOCATION OF WASTE LANDFILLS IN SOUTH TANGERANG CITY - Parwoto Parwoto; Kasman Kasman; Irwan Prasetyo; Rositayanti Hadisoebroto; Fitrio Ashardiono (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2025)
The rapid urban development of South Tangerang City, established under Law No. 51/2008, has led to significant challenges in municipal solid waste management. With a population density of 8,632 people/km² and daily waste generation reaching 972.628 tons, the city's existing landfill, Landfill Cipeucang, has experienced operational issues including a major waste slide in 2020 and ongoing community complaints about odors. These issues are exacerbated by the landfill's proximity to the Cisadane River, a critical source of drinking water, necessitating immediate action to ensure environmental and public health safety. Aim: This study aims to identify suitable alternative landfill locations to support the relocation of Landfill Cipeucang using spatial and technical criteria. Methodology and results: The method employs a spatial analysis approach through Geographic Information Systems (GIS), utilizing layering and buffering techniques based on parameters such as distance from settlements, water bodies, airports, disaster risk zones, and hydrogeological characteristics. Overlay analysis was performed to pinpoint optimal sites. The results indicated several candidate locations that meet all environmental and technical standards. Comparative evaluation among alternatives revealed the most appropriate site, considering accessibility, minimal disaster risk, and land suitability. These findings are consistent with recent landfill management research in Indonesia advocating for site relocation and innovation in waste handling. Conclusion, significance, and impact study: In conclusion, relocating the landfill based on systematic spatial and technical analysis is critical to achieving sustainable waste management in South Tangerang City and preventing further environmental degradation.